Headache due to overuse of analgesics in medical students at a private college (Research, Society and Development, 2023)
Medication overuse headache (MEC) is a chronic secondary health condition, occurring on 15 or more days per month, attributed to frequent or regular use of analgesics or acute anti-migraine medications in patients with primary headache. Prolonged medication use can be seen as a lack of adequate coping skills, including insufficient ability to cope with pain. The excessive consumption of these drugs among university students has been a major concern for public health. Based on this, the proposed objectives consisted of analyzing the incidence of headache due to excessive use of analgesics in medical students at a private university in Teresina, Piauí, identifying possible predisposing factors in this group of students. To this end, a cross-sectional, quantitative, exploratory and descriptive study was carried out. Data collection included 324 students, from the 1st to the 12th period of the course. The responses received to the questionnaire were recorded and analyzed using a Microsoft Excel spreadsheet. Based on the results obtained, there was a high percentage of students who make excessive and indiscriminate use of medication for headache (simple analgesics 71.29%, NSAIDs – 23.46%, other medications - 3.09% and opioids – 2 .16%). The immediate relief of symptoms has been the main cause of MEC, due to the cognitive and social impairment that pain can cause, however, such practice reflects in long-term effects, aggravating the condition. In view of this, it is important to carry out more research in order to explore the incidence of headache due to excessive use of analgesics among students.